2017
DOI: 10.1242/jeb.151365
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal oysters reach their physiological limit in a future high-CO2 world

Abstract: Sessile marine molluscs living in the intertidal zone experience periods of internal acidosis when exposed to air (emersion) during low tide. Relative to other marine organisms, molluscs have been identified as vulnerable to future ocean acidification; however, paradoxically it has also been shown that molluscs exposed to high CO 2 environments are more resilient compared with those molluscs naive to CO 2 exposure. Two competing hypotheses were tested using a novel experimental design incorporating tidal simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 75 publications
1
30
1
Order By: Relevance
“…Many species take months to acclimate to stressful conditions, if they acclimate at all, and thus it is possible that changes to the taste and sensory properties can only be discerned during that initial acclimation period. Although, no changes were found in this relatively short exposure study, acidification and warming has been shown to induce important physiological stress in oysters over longer exposure duration (Scanes et al, 2017;Lemasson et al, under review). While we concede that this limited exposure may not be sufficient to induce significant longterm physiological changes, some mechanisms of physiological responses, such as protein synthesis, oxygen supply, and acidbase regulation, are also involved in short-term exposures, but may not be detectable nor detrimental (Gazeau et al, 2007;Pörtner, 2008).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many species take months to acclimate to stressful conditions, if they acclimate at all, and thus it is possible that changes to the taste and sensory properties can only be discerned during that initial acclimation period. Although, no changes were found in this relatively short exposure study, acidification and warming has been shown to induce important physiological stress in oysters over longer exposure duration (Scanes et al, 2017;Lemasson et al, under review). While we concede that this limited exposure may not be sufficient to induce significant longterm physiological changes, some mechanisms of physiological responses, such as protein synthesis, oxygen supply, and acidbase regulation, are also involved in short-term exposures, but may not be detectable nor detrimental (Gazeau et al, 2007;Pörtner, 2008).…”
Section: Discussionmentioning
confidence: 64%
“…To date, only one study has looked at the effects of ocean acidification on the eating quality of seafood, and showed that future climate scenarios negatively affect the quality of northern shrimps (Pandalus borealis) by altering their sensory quality (taste and texture) (Dupont et al, 2014). Given that the physiology of adult oysters is negatively impacted by warming and acidification (Scanes et al, 2017, but see Lemasson et al, 1 http://www.fao.org/figis/. under review), it is possible that their sensory quality will reflect such changes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to distinguish the acidification signal from significant background changes, the acidification signal would need to be large. Climate change CO 2 driven changes in pH of the order of 0.1 pH units have already occurred in world's oceans and a reduction of a further 0.3–0.5 units (pH 7.8–7.6) is expected by 2100 (Scanes, Parker, O'Connor, Stapp, & Ross, ). Humic/tannic acid changes in NSW are commonly around the 0.5–1 pH unit range (OEH unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Long term, the impacts of climate change (i.e. increasing temperature and ocean acidification) not only compromise S. glomerata larval development (Parker et al 2009;Watson et al 2009) but may lower their intertidal distribution through compromised physiological performance during low-tide aerial exposure (Scanes et al 2017;McAfee et al 2018a). That said, S. glomerata has demonstrated capacity to respond to future temperature and acidification conditions (Parker et al 2011;McAfee et al 2017).…”
Section: Identifying Barriers and Solutions For Restorationmentioning
confidence: 99%